2004
DOI: 10.1038/sj.ebd.6400293
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride gel inhibits caries in children who have low caries-risk but this may not be clinically relevant

Abstract: Fluoride gel inhibits caries in children who have low caries-risk but this may not be clinically relevant Is fluoride gel effective at preventing caries in low caries-risk children?van Rijkom HM, Truin GJ, van't Hof MA. Caries-inhibiting effect of professional fluoride gel application in low-caries children initially aged 4.5-6.5 years. Caries Res 2004; 38:115-123 Design This was a double-blind randomised controlled trial (RCT) conducted over a period of 4 years. Intervention The trial used a semi-annual de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The study observed that fluoride toothpaste more than 1500ppm have superior caries preventive effect, and has also observed that caries preventive effect is higher in supervised brushing. Another research by Valeria CC Marinho,2004 7 , has concluded that topical fluorides in addition with fluoride toothpaste has modest reduction in dental caries, so both fluoride applications have better enhancement than using only fluoride toothpaste.…”
Section: Introductionmentioning
confidence: 99%
“…The study observed that fluoride toothpaste more than 1500ppm have superior caries preventive effect, and has also observed that caries preventive effect is higher in supervised brushing. Another research by Valeria CC Marinho,2004 7 , has concluded that topical fluorides in addition with fluoride toothpaste has modest reduction in dental caries, so both fluoride applications have better enhancement than using only fluoride toothpaste.…”
Section: Introductionmentioning
confidence: 99%
“…Drinking water containing fluoride has both beneficial and detrimental effects on human health [12]. The beneficial effect on the calcification of dental enamel and maintenance of healthy bones considered in the acceptable range of fluoride concentration (1-1.5 mg L -1 ) [13]. On the other hand, consumption of water containing fluoride concentration above the World Health Organization (WHO) guideline value (1.5 mg L -1 ) leads to various health effects viz.…”
Section: Introductionmentioning
confidence: 99%